Investigating the spillover effect of traditional and modern currency market with the Tehran Stock Exchange index - shima javaheri (فصلنامه بورس اوراق بهادار, 2025)
The aim of the study is to investigate The spillover effects of traditional and new financial markets (stock market, cryptocurrency and foreign exchange) by VAR model during the period of 5/2/2012 to 10/1/2023. Knowing the relationships between financial markets is a necessary issue for investors to make appropriate decisions. This knowledge can help policymakers in policy design and investors in predicting fluctuations. The results of this research show that 1) Bitcoin is not affected by the foreign exchange market and the Iranian stock exchange; Also, this market does not have a significant effect on the two foreign exchange markets and the stock market, so investors can choose the cryptocurrency market for investment in order to cover the portfolio risk. 2) The currency market and the stock market have a mutual influence on each other, although the influence of the currency on the stock market is greater and faster, but the influence of the stock market on the currency is less; According to the results of this research, it is necessary for the Two politicians in Foreign exchange and capital market to coordinate their policies so that both markets have the least turbulence, On this basis, it is necessary to coordinate capital market and currency market policies.